Cloning of the GOX-Xho Gene IPBCC 08.610 into Plasmid pTA2 and Its Characterization - Aryani, Hanifah; Akbar, Nadhira Fathiaz; Fuad, Asrul Muhamad; Ambarsari, Laksmi; Kurniatin, Popi Asri (Department of Chemistry, Faculty of Science and Technology Syarif Hidayatullah Jakarta State Islamic University, 2024)
Glucose oxidase (GOX) from Aspergillus niger catalyzes the oxidation of β-D-glucose to δ-gluconolactone and hydrogen peroxide, making it valuable for industrial applications. Intracellular GOX exhibits higher activity than its extracellular counterpart. This study focuses on enhancing the extracellular production of GOX through recombinant DNA technology. This study aimed to reconstruct the GOX gene by adding XhoI sites at both ends, inserting a glu-ala-glu-ala spacer at the 5' end, and introducing an XbaI site at the 3' end. These modifications facilitate the cloning of the GOX-Xho gene into the pTA2 vector and its subsequent ligation into the pPICZαB expression vector, allowing for extracellular production of GOX through fusion with the α-mating factor (α-MF) signal peptide. The GOX-Xho gene was successfully amplified, cloned, and characterized. The pTA2-GOX-Xho recombinant plasmid was verified through sequencing and restriction analysis, confirming the present and correct orientation of the 1797 bp GOX-Xho gene. However, sequencing revealed several point mutations, necessitating further computational analysis to predict their impact on the enzyme's structure and function before recombinant protein expression.